2000
DOI: 10.1177/102490790000700105
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Patients who Leave an Accident & Emergency Department against Medical Advice

Abstract: Patients leaving an Accident & Emergency Department against medical advice are often considered a high-risk group. A prospective study was carried out in an Accident & Emergency Department (ED) to determine the characteristics of this distinct group of patients, their reasons for leaving against medical advice (AMA), and their subsequent outcome. Telephone or personal interview of patients by a clerk was attempted within 48 hours of the visit for all patients who left Against Medical Advice (AMA) based on a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
1
15
2
Order By: Relevance
“…3 We had 115 patients who left AMA in our three months period of study with a total ED visits of 2812 concluding a prevalence rate of 4.08% which is higher than other studies. 3 The age range of patients leaving AMA was from three months to 91 years, highest in the age group of 15-44 years (65.2%) similar to other studies 1,3,[8][9][10] with slight male preponderance (54.8%) 3,9-12 which may be attributed to financial and social pressure to this group. Since health insurance system is not available in our part of world, all the health care expenses come from patients own capital.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…3 We had 115 patients who left AMA in our three months period of study with a total ED visits of 2812 concluding a prevalence rate of 4.08% which is higher than other studies. 3 The age range of patients leaving AMA was from three months to 91 years, highest in the age group of 15-44 years (65.2%) similar to other studies 1,3,[8][9][10] with slight male preponderance (54.8%) 3,9-12 which may be attributed to financial and social pressure to this group. Since health insurance system is not available in our part of world, all the health care expenses come from patients own capital.…”
Section: Discussionsupporting
confidence: 84%
“…Various studies have also concluded alcohol as one of the reasons for patients discharging AMA due to their addiction and/or impaired judgement. 3,[6][7][8]16 However, our study showed only 16% of the patients leaving AMA consumed alcohol.…”
Section: Discussioncontrasting
confidence: 63%
“…Generally speaking, depending on the patient population and the type of treatment, the rate of DAMA has varied widely, ranging from 0.7% to 2.2% for general medical admissions, 6% to 54% for psychiatric admissions [7] and 0.9% for emergency admissions [8], and as such, care must be taken in its interpretation. For example, some chronic medical problems like diabetes, hypertension (which ordinarily, with best of treatments is only controlled), tend to require longer time of care than acute conditions like malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Scarce data is available in literature on various aspects of the problem like type of cases, reasons and practice patterns of hospitals from where patients leave. The little information available comes from either single centre studies or studies in specific groups of patients especially trauma 1,6 . To get a overview of the problem, it is essential to have data from several institutions to reflect the vast and diverse spectrum of cases that leave the hospital, services provided and practices followed among them.…”
Section: Introductionmentioning
confidence: 99%